The typhoon of war : Micronesian experiences of the Pacific war - Poyer, Lin, 1953-; Falgout, Suzanne; Carucci, Laurence Marshall, 1949- (University of Hawai'i Press, 2001)
"The Typhoon of War combines archival research and oral history culled from more than three hundred Micronesian survivors to offer a comparative history of the war in Micronesia. It is the first book to develop Islander perspectives on a topic still dominated by military histories that all but ignore the effects of wartime operations on indigenous populations. The authors explore the significant cultural meanings of the war for Island peoples, for the events of the war are the foundation on which Micronesians have constructed their modern view of themselves, their societies, and the wider world. Their recollections of those tumultuous years contain a wealth of detail about wartime activities, local conditions, and social change, making this an invaluable reference for anyone interested in twentieth-century Micronesia. Photographs, maps, and a detailed chronology will help readers situate Micronesian experiences within the broader context of the Pacific War."--Jacket